Penerapan Akuntansi Manajemen Lingkungan Dalam Operasional Rumah Sakit Swasta di Kabupaten Gresik - Wahyuningtyas, Sri Harnindawati (Journal of Culture Accounting and Auditing, 2023)
The following research aims to find out the information needed related to environmental management accounting in the operational activities of a private hospital in Gresik. Research identifies physical information as well as information a number of cost for example cost processing as well as disposal waste dangerous , cost repair or conservation damaged land , cost maintenance equipment processing waste , cost doing testing emission , cost inspection content waste , cost development friendly product environment , cost development system management environment , cost evaluation and choose equipment control environment , cost production process inspection To use give guarantee will obedience on regulation environment , and environmental audit feeor monetary . The following research is a case study. The data used is a list of private hospitals in Gresik with BPJS Health patient receiving facilities. The analytical technique used is to describe the results of the questionnaires and interviews that have been carried out. Results study showthat party manager hospitals have known and understood the importance of environmental performance to realize sustainable development. Information related to environmental management accounting is divided into two, namely physical information and physical informationinformation cost / monetary, second information that required by the hospital.